2021
DOI: 10.1002/ejsp.2761
|View full text |Cite
|
Sign up to set email alerts
|

Unaccompanied refugee minors and resettlement: Turning points towards integration

Abstract: At the end of 2019, there were an estimate of 153,300 unaccompanied refugee minors (URMs) worldwide. However, due to lack of reporting, the available figures are probably highly underestimated (United Nations High Commissioner for Refugees, 2019). URMs are defined as someone under the age of 18 years who arrives without parents or other adults who cares for them, either by law or custom, to seek asylum (The Norwegian Directorate of Immigration, n.d.).Unaccompanied refugee minors are often in a state of vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Unlike Leurs's case study (2019), which found that online communication is used to strengthen family bonds across borders, the youths in this present study played games to establish or strengthen social ties with fellow unaccompanied refugee youths. Similar to the findings of research on game-based socialization, this study found that gaming might reduce feelings of loneliness (Kaye et al, 2017) that many of these youths often face (Andersson et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Unlike Leurs's case study (2019), which found that online communication is used to strengthen family bonds across borders, the youths in this present study played games to establish or strengthen social ties with fellow unaccompanied refugee youths. Similar to the findings of research on game-based socialization, this study found that gaming might reduce feelings of loneliness (Kaye et al, 2017) that many of these youths often face (Andersson et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…I needed to play with someone. young men who had lived in Norway for some time explained how gaming is an arena that offers the opportunity to mingle with other youths of similar backgrounds over an extended period, as limited friendship circles and loneliness are prevalent among this group (Andersson et al, 2021). They explained that, due to regulations related to the resettlement of unaccompanied refugee youths, their housing situation often changed, and they frequently had to move quite suddenly.…”
Section: Youths' Perception Of Their Own Gaming Practicesmentioning
confidence: 99%
“…They must re-establish their lives in an unknown culture as well as transition from adolescence to adulthood. As they are apart from their family during a crucial developmental period, URMs also need to establish new close relationships outside of their family ( Andersson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%